Prevalence of Pulpectomy In Mandibular First Primary Molar with Occlusal Caries - G, HARINI; T, DR. BHAGYA LAKSHMI; R N, DR. BALAKRISHNA (The journal of contemporary issues in business and government, 2021)
The aim of this present study was to evaluate the pulpectomy procedure in mandibular first primary molars with occlusal caries in the Chennai population visiting the Outpatient Department of Saveetha Dental College and Hospital, Chennai based on their gender and age. A total of 199 patients details aged between 4 and 11 years old obtained from patients records to assess pulpectomy treatment done with occlusal caries involved, with their gender and age. Data analysis was done with the Statistical Package for Social Sciences (SPSS) for Windows (version 20). Chi-square test was used to determine the association of occurrence pulpectomy with occlusal caries involvement in a mandibular first primary molar, gender, and age. In this present study, the prevalence of male patients was 55.78% and for females was 44.22% Males patients more prevalent for pulpectomy due to occlusal caries. Patients in the age group between 4 to 5 years old have a higher prevalence (54.77%). The most prominent teeth number affected by occlusal caries was right mandibular first primary molar-84, with 52.76% prevalence. Association between the tooth number and age of the patient. P-value=0.917, (P>0.05), association between the tooth number and the gender of the patients, P-value=0.942, (P>0.05), both of which are statistically not significant. There is no significant association between gender , age and the tooth number that was treated with pulpectomy. Within this limit of this study, this study showed that the prevalence of pulpectomy in mandibular first primary molars due to occlusal caries was more in males than females, and higher incidence for age between 4 and 5 years old, with the most affected tooth was on the right side